Joint factorial structure of psychopathology and personality. Issue 13 (5th November 2018) - Rosenström, Tom; Gjerde, Line C.; Krueger, Robert F.; Aggen, Steven H.; Czajkowski, Nikolai Olavi; Gillespie, Nathan A.; Kendler, Kenneth S.; Reichborn-Kjennerud, Ted; Torvik, Fartein Ask; Ystrom, Eivind
Abstract: Background: Normative and pathological personality traits have rarely been integrated into a joint large-scale structural analysis with psychiatric disorders, although a recent study suggested they entail a common individual differences continuum. Methods: We explored the joint factor structure of 11 psychiatric disorders, five personality-disorder trait domains (DSM-5 Section III), and five normative personality trait domains (the 'Big Five') in a population-based sample of 2796 Norwegian twins, aged 19‒46. Results: Three factors could be interpreted: (i) a general risk factor for all psychopathology, (ii) a risk factor specific to internalizing disorders and traits, and (iii) a risk factor specific to externalizing disorders and traits. Heritability estimates for the three risk factor scores were 48% (95% CI 41‒54%), 35% (CI 28‒42%), and 37% (CI 31‒44%), respectively. All 11 disorders had uniform loadings on the general factor (congruence coefficient of 0.991 with uniformity). Ignoring sign and excluding the openness trait, this uniformity of factor loadings held for all the personality trait domains and all disorders (congruence 0.983). Conclusions: Based on our findings, future research should investigate joint etiologic and transdiagnostic models for normative and pathological personality and other psychopathology.